Prospective associations between dietary patterns and cognitive performance during adolescence - Nyaradi, A.; Foster, J.; Hickling, S.; Li, Jianghong; Ambrosini, G.; Jacques, A.; Oddy, W. (Wiley-Blackwell Publishing Ltd, 2014)
Background: The aim of the study was to investigate prospective associations between dietary patterns and cognitive performance during adolescence .Methods: Participants were sourced from the Western Australian Pregnancy Cohort (Raine) Study that includes 2868 children born between 1989 and 1992 in Perth, Western Australia. When the children were 17 years old (2006–2009), cognitive performance was assessed using a computerized cognitive battery of tests (CogState) that included six tasks. Using a food frequency questionnaire administered when the children were 14 years old (2003–2006), ‘Healthy’ and ‘Western’ dietary patterns were identified by factor analysis. Associations between dietary patterns at 14 years of age and cognitive performance at 17 years of age were assessed prospectively using multivariate regression models.Results: Dietary and cognitive performance data were available for 602 participants. Following adjustment for the ‘Healthy’ dietary pattern, total energy intake, maternal education, family income, father's presence in the family, family functioning and gender, we found that a longer reaction time in the detection task (ß = .016; 95% CI: 0.004; 0.028; p = .009) and a higher number of total errors in the Groton Maze Learning Test – delayed recall task (ß = .060; 95% CI: 0.006; 0.114; p = .029) were significantly associated with higher scores on the ‘Western’ dietary pattern. The ‘Western’ dietary pattern was characterized by high intakes of take-away food, red and processed meat, soft drink, fried and refined food. We also found that within the dietary patterns, high intake of fried potato, crisps and red meat had negative associations, while increased fruit and leafy green vegetable intake had positive associations with some aspects of cognitive performance. Conclusion: Higher dietary intake of the ‘Western’ dietary pattern at age 14 is associated with diminished cognitive performance 3 years later, at 17 years.